EKSPLORASI BUDAYA SEKOLAH DAN DINAMIKA INTERAKSI TEMAN SEBAYA SEBAGAI PEMICU PERILAKU BULLYING DI SD IT AL-FATIH MAKASSAR - Syahrani Aliah Wahdini; Sulfani Padl; Zulfadli Amin; A. Muhajir Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying phenomena in elementary schools represent a serious challenge in shaping students’ character. Aggressive behaviors, both verbal and physical, often emerge due to the weak internalization of school cultural values and the imbalance of peer group interactions. This study aims to analyze the relationship between school culture, peer interaction, and bullying behavior within the context of Islamic- based elementary education, as well as to identify preventive strategies relevant to this setting. The research employed a qualitative approach with a descriptive design. Data were collected through semi-structured interviews, participatory observations, and documentation studies involving the principal, teachers, staff, and students. Data analysis utilized Miles and Huberman’s interactive model, which includes data reduction, data display, and inductive conclusion drawing. The findings indicate that a religious, disciplined, and value-oriented school culture plays a significant role in shaping students’ social behavior. However, strong peer influence remains a dominant factor contributing to bullying tendencies, particularly in the form of verbal and mild physical aggression. Teachers’ roles in addressing bullying remain reactive and are not yet supported by a structured institutional policy. The study concludes that strengthening school culture should be accompanied by constructive social interaction management through collaboration among teachers, school leaders, and parents to foster a safe, religious, and character-driven learning environment.